2006
DOI: 10.1088/0953-8984/18/39/036
|View full text |Cite
|
Sign up to set email alerts
|

Thermal enhancement of the antiferromagnetic exchange coupling between Fe epilayers separated by a crystalline ZnSe spacer

Abstract: We have put into evidence the existence of an antiferromagnetic coupling between iron epilayers separated by a ZnSe crystalline semiconductor. The effect has been observed for ZnSe spacers thinner than 40Å at room-temperature. The coupling constant increases linearly with temperature with a constant slope of ~5.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Zero-field cooling ͑ZFC͒ and field cooling ͑FC͒ routines were used in magnetization as a function of temperature measurements, as shown in Fig. 17 Langevin fittings of the M͑H͒ curve at 10 K lead to a mean magnetic moment per particle of 600 bohrs magnetons ͑ B ͒. No peak is observable in the ZFC curve indicating that even at 10 K, the sample is not magnetically blocked.…”
Section: Magnetic Characterizationmentioning
confidence: 75%
See 1 more Smart Citation
“…Zero-field cooling ͑ZFC͒ and field cooling ͑FC͒ routines were used in magnetization as a function of temperature measurements, as shown in Fig. 17 Langevin fittings of the M͑H͒ curve at 10 K lead to a mean magnetic moment per particle of 600 bohrs magnetons ͑ B ͒. No peak is observable in the ZFC curve indicating that even at 10 K, the sample is not magnetically blocked.…”
Section: Magnetic Characterizationmentioning
confidence: 75%
“…One possible explanation is that thermally activated exchange coupling, as described in Ref. 17 A weak exchange coupling with resonant character is physically reasonable between Fe nanoparticles embedded in ZnSe and is consistent with our experimental observations in the magnetization cycles and also with our previous work on such kind of structures. Indeed, Zhuravlev et al 28 have demonstrated that antiferromagnetic coupling strength, averaged over randomly distributed impurity or defect positions inside tunnel barriers, exhibits a monotonic increase with temperature when the energy of impurity or defect states matches the Fermi energy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the two modes present fingerprints of interaction between them. On the one hand, the existing gap indicates mode "repulsion" typically observed in coupled systems [37][38][39] . On the other hand, we also observed an exchange of the mode character: as observed in Fig.…”
Section: Pole Figuresmentioning
confidence: 99%
“…In the last decade, there has been great interest in the growth of ferromagnetic (FM)/semiconductor (SC)/ ferromagnetic (FM) heterostructures with inorganic [1][2][3][4][5][6][7][8][9][10][11] semiconductor spacers, due mainly to their potential in the emerging spintronics field. As a ferromagnetic electrode, most of the studies focused on either diluted magnetic semiconductors (DMS) [1][2][3] or 3d transition metals like Fe [4][5][6][7], Co [8,9], or MnAs [10,11].…”
Section: Introductionmentioning
confidence: 99%